Technology-Based Employability Curriculum and Culturally Diverse Learners With Disabilities. Issue 3 (September 2018) - Williams-Diehm, Kendra L.; Miller, Christina R.; Sinclair, Tracy E.; Wronowski, Meredith L.
As technology continues to permeate our culture and society, K–12 educators search for strategies to build student capacity and engagement with technology. Although the digital divide around access to technology has been decreasing, there is still a significant gap in the utilization of technology for educational purposes by culturally diverse learners. Even more vulnerable to unequal access to technology for educational use are culturally diverse students with a documented disability. TechNow is a promising transition-focused technology training class for high school students with disabilities. A three-factor analysis of variance revealed significant improvements in perceptions of technology skill acquisition and use of software by Latino and Native American high school students with disabilities enrolled in TechNow compared to the control group. Implications of these results suggest acquisition of critical transition skills for culturally diverse learners are enhanced through the TechNow program.